Resistance and transitional justice - Jones, Briony; Bernath, Julie (Transitional justice, 2018)
Resistance to transitional justice in the context of political violence in Côte d'Ivoire / Adou Djané dit Fatogoma -- Seeking a "just justice" : discursive strategies of resistance in Côte d'Ivoire / Briony Jones -- Between resistance to and compliance with transitional justice : the case of political decision-makers in Burundi / Sandra Rubli -- Civil society organisations and transitional justice in Burundi : when making is resisting / Gérard Birantamije -- Civil party participation and resistance at the Khmer Rouge tribunal / Julie Bernath -- Multivocal resistance to transitional justice in post-genocide Cambodia / Kosal Path -- Concluding reflections / Briony Jones and Julie Bernath